2009
DOI: 10.1523/jneurosci.1532-09.2009
|View full text |Cite
|
Sign up to set email alerts
|

Haploinsufficiency ofAFG3L2, the Gene Responsible for Spinocerebellar Ataxia Type 28, Causes Mitochondria-Mediated Purkinje Cell Dark Degeneration

Abstract: Paraplegin and AFG3L2 are ubiquitous nuclear-encoded mitochondrial proteins that form hetero-oligomeric paraplegin-AFG3L2 and homo-oligomeric AFG3L2 complexes in the inner mitochondrial membrane, named m-AAA proteases. These complexes ensure protein quality control in the inner membrane, jointly with a chaperone-like activity on the respiratory chain complexes. Despite coassembling in the same complex, mutations of either paraplegin or AFG3L2 cause two different neurodegenerative disorders. Indeed, mutations o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
99
0
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(106 citation statements)
references
References 55 publications
5
99
0
2
Order By: Relevance
“…However, the coexpression of WT and mutant AFG3L2 is able to correct the respiratory defect for most of the mutations, indicating that haploinsufficiency is the disease-causing mechanism (2). Remarkably, a partial AFG3L2 deletion (exons [14][15][16] has been recently identified as the cause of SCA28 in 2 large Belgian families, and functional studies revealed a reduced number of m-AAA complexes in these patients, demonstrating that SCA28 is due to haploinsufficiency (15). Indeed, the Afg3l2-haploinsufficient mouse resembles the phenotype of SCA28 patients, showing a progressive decline in motor performance caused by dark degeneration of Purkinje cells (PC-DCD) (16).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the coexpression of WT and mutant AFG3L2 is able to correct the respiratory defect for most of the mutations, indicating that haploinsufficiency is the disease-causing mechanism (2). Remarkably, a partial AFG3L2 deletion (exons [14][15][16] has been recently identified as the cause of SCA28 in 2 large Belgian families, and functional studies revealed a reduced number of m-AAA complexes in these patients, demonstrating that SCA28 is due to haploinsufficiency (15). Indeed, the Afg3l2-haploinsufficient mouse resembles the phenotype of SCA28 patients, showing a progressive decline in motor performance caused by dark degeneration of Purkinje cells (PC-DCD) (16).…”
Section: Introductionmentioning
confidence: 99%
“…Remarkably, a partial AFG3L2 deletion (exons [14][15][16] has been recently identified as the cause of SCA28 in 2 large Belgian families, and functional studies revealed a reduced number of m-AAA complexes in these patients, demonstrating that SCA28 is due to haploinsufficiency (15). Indeed, the Afg3l2-haploinsufficient mouse resembles the phenotype of SCA28 patients, showing a progressive decline in motor performance caused by dark degeneration of Purkinje cells (PC-DCD) (16). The latter is a specific form of a cell degeneration intermediate between necrosis and apoptosis and is characterized by cell shrinkage, cytoplasm darkening, and chromatin condensation (17).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, this mouse model seems to be adequate to unravel the pathological cascade leading to this form of SCA. 8 Notably, the six AFG3L2 mutations known so far occur in exons 15 and 16, both of which contribute to the peptidase M41 domain.…”
Section: Introductionmentioning
confidence: 99%
“…In the balance beam test, mice were trained to walk from a start platform along a 28-cm wide, 1-m long square beam suspended 50 cm above bedding (30,31). Mice were allowed to stay on the beam for a maximum of 60 s. The latency to traverse each beam and the number of times the hind feet slipped off each beam were recorded for each trial.…”
Section: Methodsmentioning
confidence: 99%